Correlation between blood glucose level and thinking concentration - Marbun, Putri Itonami Gaol; Mardiani, Tengku Helvi (Folia Medica Indonesiana, 2017)
Cognition function specifically about thinking concentration has not much yet been studied. Society view shown that glucose has role thinking quality. Few studies shown that glucose has role in specific memory quality but not in complex thinking. This study purpose to see correlation between blood glucose level with thinking concentration before eating (preprandial), after eating (postprandial), and the effect of blood glucose rise on thinking concentration. Subjects that accomplished study's requirement were recruited until forty six people and were followed within thirty minutes. Blood Glucose level was measured by glucose meter at initial admission, thinking concentration were measured with trail making test at initial admission, and compared after eating on the thirtieth minute. Descriptive analytic shown that preprandial blood glucose level in all subject is 55-119 mg/dl with 98.2 mg/dl mean. Postprandial blood glucose level in all subject is 103-171 mg/dl with 134.5 mg/dl mean. Preprandial thinking concentration in all subject is 28-93 seconds with 56.42 seconds mean. Postprandial thinking concentration in all subject is 24-73 seconds with 47.5 seconds mean. Correlation analysis showed that no significance between preprandial blood glucose level and thinking concentration (p = 0.556), postprandial blood glucose level and thinking concentration (p = 0.533), and increase in blood glucose and thinking concentration (p= 0.928). In conclusion there is no significant correlation between blood glucose level and thinking concentration.